Floods, Bushfires and Sectoral Economic Output in Australia, 1978–2014 - Ulubaşoğlu, Mehmet Ali; Rahman, Muhammad Habibur; Önder, Yasin Kürşat; Chen, Yiqun; Rajabifard, Abbas (WILEY, 2018)
© 2018 Economic Society of Australia